Rapid-Survey Methods for Flowering Phenology - Blades, Lyn; Harper, Geoffrey; Helfer, Stephan; Lee, Maria Luisa; Rogers, Liz; Stewart, Sandra (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2008)
The Weekly Phenology Project at the Royal Botanic Garden Edinburgh has been running for three and a half years at the time of writing. Insufficient data have been collected so far for scientific analysis, but we present provisional conclusions concerning several methods of monitoring flowering behaviour. These range from objective methods, such as presence/absence of open flowers and counts of flowers or inflorescences, to non-objective methods involving assessment of the degree to which full flowering has been achieved. One monitoring method, relying on the relative numbers of flowers in the three states ‘bud’, ‘open’, and ‘gone-over’, is illustrated by the flowering behaviour of ‘simultaneously’ and ‘sequentially’ flowering species. We conclude with a discussion of the relative values of the different methods.